Study of knallgas C. metallidurans CH34 as microbial chassis for aerobic CO2 fixation - Salgado, Vera Brito (2023)
The latest development on aerobic CO2/H2 fermentations relies on electrobiosynthesis using C. necator H16, where current applied directly to the culture broth yields oxygen and hydrogen at µM scale for rapidly consumption by the cells. However, formation of ROS affects culture viability and productivity and solutions so far lead to an increase in process costs. Anode electro-fermentation proves to be an interesting alternative, physically separating the culture from the final electron acceptor, connecting both only through an electric circuit. However, for this cultivation strategy, a new chassis needs to be investigated since C. necator relies on expensive redox mediators and addition of electric current to the system to perform extracellular electron transfer (EET). Cupriavidus metallidurans CH34 is closely related to C. necator H16, expressing similar oxygen-tolerant hydrogenases and cbb genes. It has also been shown to perform EET. However, it has yet to be explored in terms of aerobic CO2/H2 fermentation and as biological platform for high value products. For this end, two approaches were taken: 1) the development of an anode electro-fermentation strategy to partially bypass the flammability hazard of aerobic CO2/H2 gas fermentations using C. metallidurans native ability to form electroactive biofilms under anoxic conditions. 2) Exploration of strain engineering techniques to expand the production of high value products in C. metallidurans. In the first approach, two customised MFCs with carbon electrodes were coupled to a 1-L vessel Eppendorf bioreactor. The vessel was initially sparged with air/N2/H2/CO2 gas mixture for 24 hours, after which the mixture was adjusted to N2/H2/CO2 and the vessel continuously sparged for the remaining 346 hours. Under these conditions, C. metallidurans formed an electroactive biofilm, achieving a power density of 302.318±0.0003 mW.m-2 while fixing 549.82 ± 75.13 mmol CO2 per m2 per hour. Both power density and CO2 uptake rate significantly decreased when switched to dissolved oxygen, highliting the importance of the cathode in this system. Further optimisation achieved a power density of 360.3±4.1 mW.m-2. In the second approach, acetaldehyde and (R,R)-2,3-butanediol were attempted to be manufactured in C. metallidurans WT. However, there was no production at detectable levels in either products. Since both pathways utilise the central metabolite pyruvate as a substrate, C. metallidurans PHB biosynthesis mediated by operon phaC1AB1 was targetted to allow more availability of pyruvate. Two homologous recombination methods were used: suicide vector and P. syringae recombinases (RecE/T) mediated allelic exchange. In the former, no results were obtained. In the latter, recE and recT from Pseudomonas syringae were expressed in C. metallidurans and this resulted in the deletion of a native operon, with an editing efficiency of 84.21 ± 0.19 % within 48 hours. Further optimisation of the RecETpsy methodology in C. metallidurans using an efflux pump inhibitor increased the editing efficiency to 95.83 ± 7.22 %, again in 48 h. The generated C. metallidurans phaC1AB1 mutant was used for (R,R)-2,3-butanediol production. Again, this showed no detectable levels of product. Despite a reduced production of PHB (53.03 ± 5.10 %) in the mutant strain, there was no detectable extracellular pyruvate, which leads to believe that C. metallidurans may have some metabolic mechanisms to deal with the toxic effects of pyruvate accumulation. C. metallidurans exhibited a tight control of the central metabolite pyruvate but the strain engineering methodology developed in this work provides the necessary tools to disrupt this control, allowing production of high value products in this strain. Should this be successful, the high value production can be safely scaled-up in the anode electro-fermentation system developed using CO2/H2 as feedstock. The work presented in this thesis showcases the first steps taken to establish C. metallidurans as a chassis for CO2 fixation via anode electro-fermentation.